2018
DOI: 10.1177/0310057x1804600609
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Supplementation in Adult Patients Receiving Extracorporeal Membrane Oxygenation

Abstract: The prevalence of vitamin D deficiency in critical illness is known to be high and associated with adverse clinical outcomes. Patients receiving extracorporeal membrane oxygenation (ECMO) may be at increased risk of vitamin D deficiency due to high severity of acute illness. Challenges with drug dosing in ECMO patients are recognised due to increased volume of distribution and drug absorption to circuit components. To describe the prevalence of vitamin D deficiency in ECMO patients and the effect of intramuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It is also noteworthy that vitamin C levels are also commonly depleted in patients with sepsis and ARDS [ 314 , 315 ] and several authors have reported downregulation of NF-κB following its administration [ 316 , 317 ]. Vitamin D is also severely depleted in many patients with sepsis and ARDS [ 318 , 319 ] and dietary supplementation with this molecule also results in significant inhibition of NF-κB [ [320] , [321] , [322] , [323] , [324] ]. There is also growing interest in vitamin D supplementation in treating COVID-19 following the publication of a paper reporting severely depleted levels of this vitamin in patients with COVID-19 pneumonia and COVID-19 ARDS [ 325 ].…”
Section: Suggestions For Therapeutic Interventionmentioning
confidence: 99%
“…It is also noteworthy that vitamin C levels are also commonly depleted in patients with sepsis and ARDS [ 314 , 315 ] and several authors have reported downregulation of NF-κB following its administration [ 316 , 317 ]. Vitamin D is also severely depleted in many patients with sepsis and ARDS [ 318 , 319 ] and dietary supplementation with this molecule also results in significant inhibition of NF-κB [ [320] , [321] , [322] , [323] , [324] ]. There is also growing interest in vitamin D supplementation in treating COVID-19 following the publication of a paper reporting severely depleted levels of this vitamin in patients with COVID-19 pneumonia and COVID-19 ARDS [ 325 ].…”
Section: Suggestions For Therapeutic Interventionmentioning
confidence: 99%
“…Additionally, a single loading dose seems to be insufficient to restore vitamin D bioavailability. 78,79 Current guidelines recommend the administration of 500.000 IU of cholecalciferol within the first week in patients with severe deficiency. The COVID-19 pandemic is a new challenge for ICU nutrition on a global level.…”
Section: Indirect Calorimetrymentioning
confidence: 99%
“…Given that these patients are the most severely ill in the ICU, it is not surprising that ECLS patients have higher rates of severe vitamin D deficiency. Additionally, a single loading dose seems to be insufficient to restore vitamin D bioavailability 78,79 . Current guidelines recommend the administration of 500.000 IU of cholecalciferol within the first week in patients with severe deficiency 7 …”
Section: Introductionmentioning
confidence: 99%
“…The weight of evidence suggests that severe vitamin (Vit) D deficiency is a common occurrence in intensive care unit ( ICU ) patients with sepsis, septic shock and ARDS [ 253 , 254 ]. In addition, several authors have reported positive correlations between Vit D levels and increasing illness severity [ [253] , [254] , [255] ]. The extent of Vit D depletion also appears to be predictive of increased mortality reviewed [ 256 ].…”
Section: Suggestions For Therapeutic Interventionmentioning
confidence: 99%